Estimation and validation of spatio-temporal parameters for sprint running using a radio-based tracking system - Seidl, T.; Linke, D.; Lames, M. (Journal of Biomechanics, 2017)
Spatio-temporal parameters like step length, step frequency and ground contact time are directly related to sprinting performance. There is still a lack of knowledge, however, on how these parameters interact.